Artificial tactile sensation by microstimulation of the hindpaw representation in the primary somatosensory cortex of behaving rats - Devecioğlu, İsmail. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2016., 2016)
In this thesis, rats were trained to detect the presence or absence of bursts of mechanical sinusoidal vibrations (duration: 0.5 s, zero-to-peak amplitude: 200 m, frequency: 40 Hz) delivered to the volar surface of their hindpaws in a novel vibrotactile operant chamber. In psychophysical experiments, psychometric curves were obtained for three frequencies (40 Hz, 60 Hz and 80 Hz). Then, the rats were implanted with microelectrodes in the hindpaw representation of the primary somatosensory cortex and trained to detect trains of biphasic charge-balanced current pulses (pulse width: 600 s, current intensity: 20-200 A)(ICMS). They further tested in psychophysical experiments and psychometric curves were obtained for ICMS detection as in vibrotactile experiments. The psychometric data collected from vibrotactile and ICMS experiments were tted with surface functions using the stimulus intensity and frequency. Psychometric correspondence functions (PCFs) were constructed based on the psychometric functions of ve rats. The PCFs were used to estimate current intensities for a given tactile stimulus intensity and frequency. The PCFs were validated in an additional experiment at ve frequencies (40 Hz, 50 Hz, 60 Hz, 70 Hz and 80 Hz). In this experiment, the rats performing vibrotactile detection task were presented with unrewarded trials containing either a vibrotactile or an ICMS stimulus. The vibrotactile and ICMS intensities were matched based on PCFs. Kolmogorov-Smirnov statistic showed that the vibrotactile and ICMS stimuli produced similar psychometric curves in validation experiments (all p values >0.05 for 5 frequencies and 5 rats). Therefore, the PCF based method seems to be feasible for modulating the current intensities and frequency of ICMS in a somatosensory neuroprosthetic application.|Keywords : Vibrotactile stimulation, intracortical microstimulation, somatosensory neuroprosthesis, rat.
Keywords: Rats -- Nervous system.; Vibration -- Physiological effect.